Do retrovisor ao para-brisa: a constru????o da subjetividade identit??ria do professor - Lino, Cleonice Moreira (2018)
The present paper is inserted in the discussion about teacher education and considers subjectivity as revealing in the process of identifying the subject with his profession. The study highlights the process of identity formation of the teacher since the initial formation and that is evidenced by the subjectivity bias. It has as an hypothesis that the identity subjectivity of the teacher is constituted through a formative process that, beyond the scientific and technical contents of the area, involves the cultivation of their subjectivity. It adopted as general objective to identify the delineating processes of the teacher identity through the professional formation and revealed by the subjectivity in the performance of the egress teachers from the course of Full Degree in Mathematics from the Federal Institute of Education, Science and Technology of Piaui - IFPI - Campus Floriano. The qualitative narrative research was constituted as a case study that was given through narrative interviews made to 11 (eleven) egress of the IFPI Campus Floriano. The theoretical-methodological conception of the research brings interlaced to the theoretical reference the discursive theoretical axes: teacher formation, identity and subjectivity. Teacher training as a course traversed by the teaching professional that involves the path established and awakened in the initial formation and that extends throughout the experiential course of the pedagogical activity. Identity as built in relationships, which in time individualises the human being, gives ownership and establishes the way of being and being in the profession. Subjectivity as an internal process of the human being, triggered by social, historical, biopsychic, epistemic and cultural relations that propels or retracts it from the experiences of the world leading to actions that promote its process of subjectivation through the objective activities it practices. This study dialogues with the authors: Ardoino (1998), D'Ambrosio (1986), Fazenda (2007, 2008), Fiorentini (2005), Imbern??n (2016), Japiassu (2006), Josso (2004, 2010), Saviani (1990, 2014), Severino (1986, 1990, 2011, 2012), Leontiev (1978), Morin (2000, 2008, 2015), Moura (2002), N??voa (1992, 1995), Pineau (1988), Pimenta (2002) among others. The text discusses the teacher formation presenting mishaps and advances and explaining fundamental concepts for the understanding of the identity subjectivity clarifying complementary concepts such as: intentionality, interdisciplinarity, transdisciplinarity, multireferentiality and ethnomathematics. The final considerations emphasize that identity subjectivity plays a significant role in the intentionalising impregnation of the teaching activity and points out philosophy as necessary to the current formation that contemplates the humanism of the teacher. They also record the author's findings and understandings in an attempt to contribute to the reflections of the trainers and signals the need for further studies on the subject.